Protein analysis of the spermatophore reveals diverse compositions in both the ampulla and the spermatophylax in a bushcricket. (21st August 2017) - Lehmann, Gerlind U. C.; Lehmann, Karola; Neumann, Boris; Lehmann, Arne W.; Scheler, Christian; Jungblut, Peter R.
Abstract: Nuptial gifts are male mating investments, which, in bushcrickets, comprise the sperm‐containing ampulla and the attached spermatophylax. The functions of the spermatophylax are to deter females from premature removal of the sperm‐containing ampulla, which is a nutrient resource for females, as well as a source of compounds that influence female behaviour to increase male evolutionary fitness. Placing these functions into a proteomic perspective, we analyze the protein composition of nuptial gifts from male Poecilimon ampliatus (Brunner von Wattenwyl, 1878) bushcrickets using large two‐dimensional gel electrophoresis coupled with nano‐liquid chromatography‐electrospray ionization mass spectrometry and de novo sequencing. We separate the proteins with high resolution and detect approximately 600 protein spots in the seminal fluid (ampulla) and 300 in the spermatophylax. There is only a small fraction of overlap in protein spots, whereas the majority differ between the two compartments. As a result of the lack of a sequenced genome and protein data for this non‐model insect, we are unable to identify the proteins. We discuss the diversity of proteins, as well as their size range, in light of potential protein costs and potential functions. Abstract : Bushcrickets transfer large spermatophores made of the sperm‐containing ampulla and the attached spermatophylax. This nuptial gift is a nutritious and nitrogen‐rich source for females. Using large two‐dimensional gel electrophoresis, we separate the proteins with high resolution and detect approximately 600 protein spots in the ampulla and 300 in the spermatophylax. Only a small fraction of protein spots are detected both in the ampulla and in the spermatophylax, whereas the majority differ between the two compartments.